Stating a Popular Life Science: ancestry and Agroecology in the Formulation of Rural Education Science Teaching (Countryside) - Marcelo Vaz Pupo (Universidade Federal do Norte do Tocantins, 2018)
The purpose of this article is to propose, from historical and conceptual aspects, a science teaching for Rural Education. For this task, we analyzed some historical facts with the purpose to present a popular view of the environmental problems in the western world, highlighting the role of biocultural memory in the sustainability of the planet. Subsequently, a resumption of the Life Sciences in its formulation process was made throughout the nineteenth century, correlating them with the projects of society in dispute. Recognizing the agro-industrial way of appropriating ecosystems as a producer of irreparable metabolic failures in the relationship between society and the environment, we finally established a science education that makes Agroecology and the modes of appropriation of agroecosystems central elements of analysis and pedagogical guidance.